Proceedings of the LST International Cohference on Geography and Education (ICGE 2016) 2017
DOI: 10.2991/icge-16.2017.43
|View full text |Cite
|
Sign up to set email alerts
|

Landsat Image Analysis for Open Spaces Change Monitoring to Temperature Changes in Semarang City

Abstract: Land use change in urban areas could not be avoided as consequence of land requirement incensement. The high density of developed land in the central city have pushed the development towards the periphery. This article examines the result of Landsat image analysis using remote sensing (RS) and geographic information system (GIS) technology to monitor green open spaces change to temperature changes in Semarang. Data source which used in this study are Landsat 5 Image in 2003, and Landsat 8 Image in 2015. This u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…So, from these data, it can be concluded that an increase of 2,851.50 ha or about 10.27% in the last 19 years (2000 -2019). An increase in the area of developed land that is not restricted can result in environmental degradation [14]. Figure 3 presents the trendline of landcover change in Rawapening DTA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, from these data, it can be concluded that an increase of 2,851.50 ha or about 10.27% in the last 19 years (2000 -2019). An increase in the area of developed land that is not restricted can result in environmental degradation [14]. Figure 3 presents the trendline of landcover change in Rawapening DTA.…”
Section: Resultsmentioning
confidence: 99%
“…The use of remote sensing data (Landsat imagery) is an effective and efficient means for obtaining information about land cover, including for assessing catchment areas [12]- [17]. Landsat satellite imagery has been widely used for various survey activities because it has several advantages including its excellent temporal resolution making it easy to process information on the development of land cover in an area [12], [14], [15]. This study aims to examine the development of built-up land in the Rawapening catchment area from 1990 to 2019 and then link the result to the increased sedimentation that occurred in Rawapening Lake.…”
Section: Introductionmentioning
confidence: 99%
“…Akibatnya, banyak terjadi degrasi lingkungan dan konversi lahan untuk menunjang kebutuhan manusia (Wilonoyudho, 2014). Studi sebelumnya telah mengungkapkan bahwa Kota Semarang telah mengalami perubahan tutupan lahan yang signifikan sehingga menyebabkan peningkatan suhu (Nugraha, Sidiq, & Hanafi, 2016). Oleh karena itu, sangat penting untuk mengelola dan mengevaluasi konsekuensi negatif dari urbanisasi dan perubahan penggunaan lahan/tutupan lahan untuk menggapai sasaran kota yang berkelanjutan.…”
Section: Pendahuluanunclassified
“…Penelitian sebelumnya sudah mengkaji dinamika suhu di kota Semarang dari waktu ke waktu (Nugraha et al, 2016). Namun, belum diteliti lebih lanjut mengenai aspek kenyamaan dari aspek suhu terkait dari konsekuensi penurunan kondisi ekologis perkotaan.…”
Section: Pendahuluanunclassified
“…This happened as a result of a land use change due to the increasing need for building land. It was further revealed that changes in open land become built area could affect the environment in various ways, including the high temperature of land's surface surrounding the built area [9], [17], [20].…”
Section: Introductionmentioning
confidence: 99%